Neoapterocis, a new genus of apterous Ciidae (Coleoptera: Tenebrionoidea) from Chile and Mexico - Lopes-Andrade, Cristiano (Zootaxa, 2007)
Neoapterocis gen. nov. is described based on two species: Neoapterocis mexicanus sp. nov. (type species) from the state of Oaxaca (Mexico); and Neoapterocis chilensis sp. nov. from Concepción Province (VIII Biobío Region), Chile. Diagnostic characters of the genus include the distinct oval, highly convex body, small eyes and scutellum, absence of hind wings, short prosternum and metaventrite, and first abdominal ventrite longer than the next two together. Comparisons are made with other apterous and micropterous ciid genera, particularly Apterocis Perkins, Lipopterocis Miyatake, Nipponapterocis Miyatake and Polynesicis Zimmerman. The new genus is placed in the tribe Ciini. A key to males of the species of Neoapterocis gen. nov. is provided, together with descriptions of external morphology of adults, morphology of male genitalia of both species and the female genitalia of Neo. mexicanus sp. nov. Neoapterocis gen. nov. is the first apterous ciid genus to be described from continental lands